Does Qatar Face a Trade-off Between Economic Growth and CO2 Emissions? - Shannak, Sa'd; Contestabile, Marcello (Frontiers in Environmental Science, 2022)
Qatar has made remarkable economic achievements over the past few decades. However, the country has one of the highest per capita carbon dioxide emissions at 37 metric tons per person. As such, the country is facing a trade-off between boosting economic growth and lowering carbon dioxide emissions. This study empirically analyzes the relationship between economic growth and carbon emissions in Qatar, using annual data of income and CO2 carbon emissions from 1970 to 2018. The analysis was conducted by employing the Environmental Kuznets Curve (EKC) framework and the Decoupling Index (DI) approach. The EKC was evaluated using the Fully Modified Ordinary Least Squares cointegration method. Additionally, a robustness check was conducted by Canonical Cointegrating Regression (CCR) cointegration method to confirm the results attained by FMOLS. The findings of this study show that in Qatar, there is evidence for the N-shaped relationship, the country is also going under expanding relative decoupling. Although findings show that Qatar’s total emissions have been declining over the last few years, additional energy efficiency, diversifying the energy mix by introducing more renewable and implementing energy demand management programs are necessary to maintain the same trend of decline and achieve climate change objectives.